2014
DOI: 10.4236/ojce.2014.44028
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Pit-Sand on Resistance Capacities of Reinforced Concrete Space Framed Structures

Abstract: This paper used the existing formulae in estimating resistance parameter of reinforced concrete structure to assess the effect of concrete produced from pit-sand in Akure metropolis, on the resistance parameters of a collapsed building in Oba-Ile, Akure. Site inspections were carried out on the collapsed building, and concrete samples were taken. Both destructive and non-destructive methods were used to determine the structure's concrete strength. The number of reinforcements in each structural element was det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…Reinforced concrete beams can fail by bending, by shearing or by flexural-shearing mode of failures. Olanitori and Afolayan (2014) noted that, most reinforced concrete structures failed by shearing, and this is because there exist discrepancies between estimated shear capacity based on equations from the codes and, the actual shear capacity and concluded that more research work should be conducted on models that can predict the shear capacity of reinforced concrete beams more accurately. Olanitori and Olotuah (2005), noted in their study, that targeted concrete strength may not be achieved due to the silt/clay content in the fine aggregate.…”
Section: Olanitori Lm; Gbadamosi Iamentioning
confidence: 99%
“…Reinforced concrete beams can fail by bending, by shearing or by flexural-shearing mode of failures. Olanitori and Afolayan (2014) noted that, most reinforced concrete structures failed by shearing, and this is because there exist discrepancies between estimated shear capacity based on equations from the codes and, the actual shear capacity and concluded that more research work should be conducted on models that can predict the shear capacity of reinforced concrete beams more accurately. Olanitori and Olotuah (2005), noted in their study, that targeted concrete strength may not be achieved due to the silt/clay content in the fine aggregate.…”
Section: Olanitori Lm; Gbadamosi Iamentioning
confidence: 99%
“…The sand should be free from impurities like clay, silt and organic matter, (BS EN 13139). A high content of clay and silt causes a significant reduction in the compressive strength of the concrete (Olanitori, 2006). The Mfs is one of the physical properties of sand (Purwandito et al, 2018) and is used in specifying the proportions of fine and coarse aggregates when designing concrete mixes (Dhir et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Also, Olanitori and Afolayan [21], in their investigative work on the causes of the collapse of a building which was detailed and constructed as rigid joints in Nigeria, noted that the actual shear capacity of the building was 18.88 kN, while the predicted shear capacity was 64.4 kN. This wide variance of about 241% between the actual and predicted shear capacities calls for more research into the behavior of reinforced concrete space-framed structures.…”
mentioning
confidence: 99%